Status of Phenolics and Amino Acids in Leaf of Thompson Seedless Grapes Grafted on Different Rootstocks under Indian Condition (Global Journal of Science Frontier Research, 2012)
The study on status of phenolics and amino acid content in leaf of 8 years old Thomson Seedless grapes grafted on different rootstock was conducted during the year 2008 - 2009. Leaf samples were collected at different growth and development stage of a vine. The status of phenols and amino acid at four major growth stages in the leaf of Thompson Seedless grapevine grafted on different rootstocks using high performance liquid chromatography was studied. The differences for phenolic compound at different stages were observed. The accumulation of amino acid in leaf in grape rootstock was found to be stage specific. The concentration of phenolic and amino acid was found to be increased and decreased from one stage to another and was more specific in different rootstocks showing that individual rootstock has capacity to synthesize their food differently.